STUDI PENELURUSAN KINERJA PENGELOLAAN SARANAPRASARANA DAN SISTEM MANAJEMEN LABORATORIUM IPA PADA TINGKAT MADRASAH TSANAWIYAH (MTs) SEKABUPATEN JENEPONTO - Muh Said L. (Teknosains, 2014)
This research about study sighting of fasility and laboratorymanagement of Natural Sciences. at level of Madrasah Tsanawiyah(MTS) Se-Kabupaten Jeneponto. This formula research internal issueis (1) What is the equipment of laboratory facilities and basic facilitiesof Natural Sciences. by school of madrasah se-Kabupaten Jenepontofulfill minimum standard which specified by Institute StandardNational Education?; ( 2) How is laboratory management of NaturalSciences by existing MTS se-Kabupaten Jeneponto?; This researchhave been conducted with a few method intake of data that isobservation, admission filling of enquette, direct interview anddocumentation photograph result of survey. Data analysis in thisresearch is used analytic descriptive method that is intake ofquantitative data, then analysed descriptive statistically.Result of research obtained that (1) laboratory facilities and basicfacilities of natural sciences by the school of madrasah MTS se-Kabupaten Jeneponto not yet fulfilled minimum standard whichspecified by Institute Standard National Education and not yet ismaximal of management performance meanly; ( 2) Laboratorymanagement system of natural sciences by existing MTs obtainedmeanly assess the understanding of interest standard lead laboratorythat is 3,14 namely good category, but application in streamliningactivity of management of laboratory not yet maximal and not yetaccording of attainment goals.